2012
DOI: 10.1108/17410401211194671
|View full text |Cite
|
Sign up to set email alerts
|

Identifying productivity blemishes in Pakistan automotive industry: a case study

Abstract: PurposeThe purpose of this research is to identify the prevalent condition of productivity in the automotive manufacturing industry of Pakistan and to indicate the possible areas for enhancing productivity.Design/methodology/approachSecondary data for the last ten years were gathered. Total productivity and all partial productivities were computed using methodology proposed by Sumanth, and total factor productivity (TFP) was computed using Cobb‐Douglas production function. Regression analysis and Pearson corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…To enhance the explanatory value of the productivity variable, in future research, the following proven equations [94] may be used. Q = ALαKβ.…”
Section: Future Workmentioning
confidence: 99%
“…To enhance the explanatory value of the productivity variable, in future research, the following proven equations [94] may be used. Q = ALαKβ.…”
Section: Future Workmentioning
confidence: 99%
“…Zahoor Sarwar et al . (2012) studied the productivity status and trend in Indus Motors and Honda Atlas over a span of ten years, from 2000 to 2010.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Then, they calculated partial productivities such as labor productivity, material productivity, and capital productivity and total productivity. They found low levels of labor productivity and capital productivity causing huge losses and no growth in those firms (Zahoor Sarwar et al ., 2012). Since only two automotive manufacturing facilities were used (Indus Motors and Honda Atlas), the findings may not be generalized to many other automotive plants.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While probing into the current scenario of automotive manufacturing industry its productivity and possible remedies to improving the productivity, Sarwar et al (2012) found that the effective usage of technology can enhance productivity. Tanveer et al (2012) during the investigation of declining market share of Pakistani football manufacturing industry mentioned that customers prefer those suppliers who can adopt quickly to new technology and simplified processes for production, cost reduction and those who possess the JIT capabilities with lower inventory.…”
Section: Literature Reviewmentioning
confidence: 99%